The congenital clubfoot – immunohistological analysis of the extracellular matrix - Kerling, Arno (Orthop Res Rev, 2018)
PURPOSE: Congenital clubfoot is one of the most common limb disorders in humans and its etiology is still unclear. In order to better understand the pathogenesis of patients with primary clubfoot, we examined whether there are quantitative changes in the extracellular matrix (ECM; based on common interstitial collagens [C] like CI and CIII, microfilamentous collagens like CVI, noncollagenous proteins like undulin, and enzymes like matrixmetalloproteinase [MMP]-2 and tissue inhibitor of matrixmetalloproteinase [TIMP]-2 that are known to play a role in fibrogenesis and fibrolysis) of muscles involved in the foot deformity of patients with primary clubfoot corresponding to fibrosis. PATIENTS AND METHODS: Thirty patients (age ranging from 4 months to 5 years and 7 months) with primary clubfoot were examined (23 male and 7 female patients), among whom 18 patients were affected on one side and 12 affected on both sides. Twenty-five biopsies were taken during the first operative foot correction (Crawford–McKay) and 5 in the context of relapses. Muscle biopsies were taken from the muscles involved in the defect (Musculus [M.] gastrocnemius and M. tibialis anterior) and from the M. vastus lateralis of the M. quadriceps femoris, which were treated as healthy comparison muscles. Quantitative analysis of the components of the ECM was performed using a computer-assisted fibrosis measurement of the immunohistochemically processed tissue samples. RESULTS: We found higher values for M. gastrocnemius for CI, CIII, CVI and undulin in comparison with M. vastus lateralis. However, values for TIMP-2 were reduced. We found no significant differences for the components of M. tibialis anterior and M. vastus lateralis. There were no quantitative differences between male and female or between patients affected on one side and both sides. In patients who underwent relapse surgery, CI, CIII, CVI, and undulin of the gastrocnemius were significantly higher, while TIMP-2 was significantly lower. CONCLUSION: In the present study, we found manifest fibrosis in gastrocnemius due to quantitative changes in the ECM. In contrast to other studies, we found increasing fibrosis not just in contracted tissues but also in the muscle itself. Further studies are needed to clarify whether these changes are primarily responsible for the malfunction or whether they occur secondarily in the consequence of the dysfunction.